Integrated Modeling and Mult objective Control of Multilevel DC/AC Inverters for Conducted Electromagnetic Interference Mitigation (Al-Farooq Journal of Sciences, 2026)
Multilevel DC/AC inverters have become a major enabling technology for renewable energy systems, electric vehicles, smart grids and industrial motor drives since they can produce high-quality output voltages with lower switching stress and higher power conversion efficiency. However, the impulse HMIs but also high-frequency switching actions and complicated modulation processes used in the more advanced multilevel inverter topologies result in undesirable high amplitude conducted EMI appearing at their terminals, which can severely affect electromagnetic compatibility (EMC), system reliability, power quality and compliance with international regulatory standards. Passive Filtering Techniques or Conventional EMI mitigation approaches which is primarily relying on passive filtering techniques and also adds to the size, cost and power losses in the system due to reduced adaptability under diverse operating conditionsThe research proposes an integrated model and Mult objective control framework for conduction EMI mitigation in multilevel DC/AC inverters. An exhaustive mathematical model is designed to describe the inverter switching dynamic, parasitic element contribution, common-mode voltage generation and differential-mode disturbances propagation processes as well as EMI propagation mechanisms. A Mult objective optimization strategy is then proposed to minimize the conducted EMI emissions, overall total harmonic distortion (THD), switching losses and common-mode voltage in conjunction with high conversion efficiency and stable inverter operation based on the established mathematical model. Advanced control and modulation techniques are embedded in the optimization framework to achieve optimal balancing of conflicting performance objectives.The offered method is verified in extensive simulation experiments taken on a number of operating conditions. Performance assessment is performed via frequency-domain and time-domain analyses, with results compared to traditional control designs and EMC criteria. The framework supports systematic identification of the best operating points via Pareto optimization and serves as an effective design tool in balancing EMI suppression, power quality, and energy efficiency. The research supplies a complete EMI-aware inverter design method to assist the development of high-performance, EMC-compliant energy digital structures for next-generation power conversion applications.
Keywords: Multilevel DC/AC Inverters; Conducted Electromagnetic Interference (EMI); Electromagnetic Compatibility (EMC); Mult objective Optimization; Common-Mode Voltage; Total Harmonic Distortion THD; Advanced Control Strategies; Pareto Optimization; Power Electronics: Renewable Energy Systems